Optimization Of Injection Moulding Process For Hdpe Moulded Gear - Kassim, Mohd Syahir Mohd (2015)

(untitled)
Nowadays, the world's plastic usage has drastically increased in various applications of product. As demand, a high speed production is requires to sustain the market needs. Consequently, all plastic manufacturers are struggling to maintain the quality of moulded product and they are also burdened with plastic waste management issues related to the efficient disposal of the post-industrial waste. Numerous efforts have been done to facilitate the plastic recycling to a greater extent in solving the plastic disposal issues as well as quality improvement of moulded product. In this research, the feasibility of multiple recycle HDPE is investigated based on their dimensional stability, mechanical and rheological properties. The optimization of the injection moulding processing parameters for HDPE gear is presented via integration of Taguchi method with principal component analysis (PCA). Considering the functionality of the plastic gear, the shrinkage rate (tooth thickness, addendum and dedendum circle) and tensile properties (ultimate strength, Modulus Young, and elongation at maximum load) are selected as the performance response. A screening experiment was conducted with an L18 orthogonal array (OA) to screen out the significant parameters involved. Later, the optimal parameters and interaction effect is identified via optimization experiment with the used of L27 OA, PCA, main effect analysis and analysis of variances (ANOVA). As a result, the shrinkage characteristics and tensile properties of moulded gear are optimized simultaneously. Finally, the obtained optimal parameter settings were used in feasibility experiment in order to evaluate the performance of multiple recycle HDPE. The results depict that reprocess cycle at 3rd to 7th have the optimal condition which closes to virgin HDPE performance. The experimental findings show the effectiveness of the integration Taguchi method with PCA in optimizing parameter settings has proved and also improve the multiple quality characteristics of HDPE moulded gear simultaneously with minimum number of experiment.